البنية المكانية في رواية الانتفاضة الكبرى لعلال عثمان - مردف, سعد; معلم, خولة; مرغني, عفاف; جرمون, مريم (University of Eloued جامعة الوادي, 2024)
المكان تاريخيا أقدم من الإنسان، والإنسان بوجوده وكينونته في المكان يعيد تشكيله وتحويله إلى أشكال مختلفة حسب احتياجاته الحياتية والثقافية. بحيث يرى الدارسون أن العمل الأدبي حين يفتقد المكانية فهو يفتقد خصوصيته وبالتالي أصالته؛ فالمكان في النص الروائي يتجاوز كونه مجرد خلفية تقع عليها أحداث الرواية فهو العنصر الغالب فيها والحامل للدلالة ويمثل محورا أساسيا تدور حوله باقي العناصر الفنية الأخرى. The place is historically older than man, and man, by his presence and being in the place, reshapes it and transforms it into different forms according to his life and cultural needs. So that scholars see that when a literary work lacks spatiality, it lacks its specificity and thus its originality. The place in the fictional text goes beyond being just a background on which the events of the novel take place. It is the dominant element in it, the bearer of meaning, and represents a basic axis around which the rest of the other artistic elements revolve.
أدب حديث ومعاصر
Keywords: المكان، الرواية، البنية المكانية، المكان المغلق، المكان المفتوح.; Place; novel; spatial structure; closed place; open place.